CREATION OF ASSESSMENT INSTRUMENTS IN DIFFERENTIAL LEARNING SYSTEMS (Universitas Pendidikan Indonesia, 2024)
The purpose of this study is to make an assessment that will be made in the form of an instrument performance assessment and multiple choice assessment instrument assessment with differential system material, by conducting a validation test on expert lecturers and vocational high school teachers. The type of method taken in this study is the Research and Development method with the 4D model, a research method used to produce products and test the effectiveness of the product. The population taken in this study were 30 students of class XI Automotive Light Vehicle Engineering (TKRO) with a purposive sampling technique. The preparation of this assessment instrument was validated by experts who were 2 expert lecturers and 3 teachers of the Automotive Light Vehicle Engineering Vocational High School. The testing carried out was in the form of a validity test using the Content Validity Ratio (CVR) and Content Validity Index (CVI) formulas and cognitive assessments using the Anatest program. Obtaining CVR results on 20 items of differential system practice activities were declared valid and 2 items of activities were declared invalid, while for the CVI results in this study, the value was 0.92 which was declared